2010
DOI: 10.1088/0022-3727/43/32/325004
|View full text |Cite
|
Sign up to set email alerts
|

Analytical expression of the magneto-optical Kerr effect and Brillouin light scattering intensity arising from dynamic magnetization

Abstract: Time-resolved magneto-optical Kerr effect (MOKE) and Brillouin light scattering (BLS) spectroscopy are important techniques for the investigation of magnetization dynamics. Within this article, we calculate analytically the MOKE and BLS signals from prototypical spin-wave modes in the ferromagnetic layer. The reliability of the analytical expressions is confirmed by optically exact numerical calculations. Finally, we discuss the dependence of the MOKE and BLS signals on the ferromagnetic layer thickness.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Figure 5 illustrates the calculated specific MOKE rotation and ellipticity for the 15 nm-thick Fe films. The data were calculated using the layer-by-layer approach based on the medium boundary and propagation matrices [2][3][4][5] for the p-polarized incident beam.…”
Section: Supplementary Note 2: Moke In-depth Sensitivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 5 illustrates the calculated specific MOKE rotation and ellipticity for the 15 nm-thick Fe films. The data were calculated using the layer-by-layer approach based on the medium boundary and propagation matrices [2][3][4][5] for the p-polarized incident beam.…”
Section: Supplementary Note 2: Moke In-depth Sensitivitymentioning
confidence: 99%
“…
Spintronics had a widespread impact over the past decades due to transferring information by spin rather than electric currents [1][2][3][4][5][6]. Its further development requires miniaturization and reduction of characteristic timescales of spin dynamics combining the sub-nanometer spatial and femtosecond temporal ranges [7].
…”
mentioning
confidence: 99%
“…This technique combines photo and spin-wave excitation, hence the 720 term photo-magnonics. A recent work by Hamrle showed that both optical techniques, BLS and TRMOKE are comparable in their sensitivity [64].…”
mentioning
confidence: 99%
“…In order to optimize the optical detection either for magneto-optical imaging or in time-resolved experiments, it is important to determine the wavelength dependence of the MOKE. However, the MOKE is also dependent on the layer thickness, the layer and substrate indices, all the more in weakly absorbing magnetic materials as semiconductors or insulators [21][22][23][24]. It is therefore of prime importance to retrieve the intrinsic magneto-optical parameters, depending only on the bulk material structure.…”
Section: Introductionmentioning
confidence: 99%